STUDIES ON THE LARVICIDAL EFFICACY OF LEAF EXTRACT OF VITEX NEGUNDO AGAINST CULEX QUINQUEFASCIATUS - POONGUZALI J; KALAIVANI M (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Mosquitoes are one of the most significant vectors among arthropods. Infection due to mosquito plays a major health problem in developing countries. Repeated use of synthetic insecticides for mosquito control has disrupted natural biological control systems and led to resurgences in mosquito populations. Plants may be an alternative source of mosquito control, potential as insecticide. Controlling of mosquitoes at the larval stage is easy, as target specificity of the larvicide used can be ensured. Methods: The present study has assessed the role of larvicidal activity of aqueous, chloroform, and methanol leaf extracts of Vitex negundo plant against first, second, third, and fourth instar larvae of Culex quinquefasciatus. Mortality rates were recorded after 24 h and 48 h to evaluate the larvicidal activity against C. quinquefasciatus. Results: Among the three extracts, the methanol extract was found to be the most effective providing 86.67% mortality at 200 ppm concentration against the larvae of C. quinquefasciatus, when compared with aqueous and chloroform extracts, where the mortality rate is 83.33% and 70.00%, respectively. Conclusions: The results therefore clearly indicate that V. negundo leaf extracts possess larvicidal activity against the larvae and could be a possible source of mosquito larvicides.